Feeding during the rest phase promotes circadian conflict in nuclei that control energy homeostasis and sleep–wake cycle in rats. (24th April 2017) - Ramirez‐Plascencia, Oscar D.; Saderi, Nadia; Escobar, Carolina; Salgado‐Delgado, Roberto C.
Abstract: Food intake during the rest phase promotes circadian desynchrony, which has been associated with metabolic diseases. However, the link between circadian rhythm and metabolic alterations is not well understood. To investigate this issue, we explored the circadian rhythm of c‐Fos immunoreactivity (IR) in rats fed during the day, during the night or with free access to food for 3 weeks. The analysis was focused on the hypothalamic nuclei, which are interconnected and involved in the control of energy homeostasis and/or arousal: lateral hypothalamus (LH), perifornical area, arcuate, ventrolateral pre‐optic (VLPO) and tuberomammillary nuclei. The results show that food intake during the rest phase flattened the circadian c‐Fos expression in the LH and perifornical area, and induced a phase shift in the VLPO area. In addition, c‐Fos expression was analyzed in the orexin and melanin‐concentrating hormone (MCH) neurons of the LH, which are involved in the control of food intake and arousal, and in α‐melanin‐stimulating hormone and neuropeptide Y (NPY) cells in the arcuate nucleus, all of which are involved in feeding–fasting cycles, energy homeostasis and sending projections to the LH. The results indicate that feeding during the rest phase decreased orexin neuron activation in the light in comparison with the other groups. Feeding during this phase also flattened the activity rhythm of MCH and α‐melanin‐stimulating hormone neurons and increased NPY IR when the light was turned on. This evidence indicates that mealtime differentially affected the hypothalamic nuclei under investigation leading to a circadian conflict that might account for metabolic impairment. Abstract : Human night workers are prone to eat during the night and to develop metabolic syndrome. In murine models of night work, in which rats have food during the rest (light) phase, the circadian rhythm of c‐Fos/α‐MSH co‐expression is flattened, ORX and MCH/c‐Fos co‐expression suffer a phase advance, and c‐Fos rhythm in the VLPO also exhibits a phase advance. Thus, food intake in the rest phase promotes circadian shifts in hypothalamic nuclei and their main neuropeptides involved in metabolism and arousal.